(untitled) (Afaq Lughawiyyah, 2024)
Learning strategies are techniques or steps taken by students to help them facilitate the acquisition and mastery of a language. In the context of language learning, it involves conscious thinking and behavior used by students to launch a language learning process. The previous study prove that the Arabic language learning strategy among students is at a moderate level and it can affect the student’s learning outcomes. This study examines the relationship between learning strategies and Arabic learning outcomes among religious secondary school students in Malaysia. For this purpose, a set of Likert scale-type questionnaires was distributed to 500 form four students who were selected using a random sampling technique from 20 religious secondary schools according to the zones in Malaysia. This quantitative study uses descriptive and inferential data analysis. The findings of the study show that the level of students’ learning strategies as a whole is at a mean value of 3.64 (SD = 0.39) which is at a moderately high level. The findings of the study also show that there is a significant relationship between learning strategies and students’ Arabic learning outcomes (r=0.668, p>.05) at a significant level of 0.01. The findings of this relationship show that the learning strategies practiced by students can affect the results of their Arabic learning at school.